2000
DOI: 10.1073/pnas.97.9.4932
|View full text |Cite
|
Sign up to set email alerts
|

Brain size does not predict general cognitive ability within families

Abstract: Hominid brain size increased dramatically in the face of apparently severe associated evolutionary costs. This suggests that increasing brain size must have provided some sort of counterbalancing adaptive benefit. Several recent studies using magnetic resonance imaging (MRI) have indicated that a substantial correlation (mean r ‫؍‬ Ϸ0.4) exists between brain size and general cognitive performance, consistent with the hypothesis that the payoff for increasing brain size was greater general cognitive ability. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 38 publications
0
57
0
1
Order By: Relevance
“…From the results presented here, we may hypothesize that children with suboptimal HC may have alterations of brain development which become associated with the lowered SES, SA and IA, variables that in the current study contributed to determine the educational results; independent of SES and sex, differences in human brain size are relevant to explain differences in intelligence test performance (Ivanovic et al, 1996(Ivanovic et al, , 2000a(Ivanovic et al, , b, c, 2001(Ivanovic et al, , 2002(Ivanovic et al, , 2004aReiss et al, 1996;Botting et al, 1998;Strauss and Dietz, 1998;Toro et al, 1998;Pennington et al, 2000). These studies found positive and significant correlations between HC, SA, IA, brain and parental HC; however, an absence of correlations between brain size, HC and intelligence has been reported in studies of monozygotic twins or in sisters (Tramo et al, 1998;Schoenemann et al, 2000). Other studies have concluded that head size at an early age is a good predictor of later intelligence, learning, cognition and concentration at school age (Botting et al, 1998;Strauss and Dietz, 1998;Stathis et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…From the results presented here, we may hypothesize that children with suboptimal HC may have alterations of brain development which become associated with the lowered SES, SA and IA, variables that in the current study contributed to determine the educational results; independent of SES and sex, differences in human brain size are relevant to explain differences in intelligence test performance (Ivanovic et al, 1996(Ivanovic et al, , 2000a(Ivanovic et al, , b, c, 2001(Ivanovic et al, , 2002(Ivanovic et al, , 2004aReiss et al, 1996;Botting et al, 1998;Strauss and Dietz, 1998;Toro et al, 1998;Pennington et al, 2000). These studies found positive and significant correlations between HC, SA, IA, brain and parental HC; however, an absence of correlations between brain size, HC and intelligence has been reported in studies of monozygotic twins or in sisters (Tramo et al, 1998;Schoenemann et al, 2000). Other studies have concluded that head size at an early age is a good predictor of later intelligence, learning, cognition and concentration at school age (Botting et al, 1998;Strauss and Dietz, 1998;Stathis et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These correlations seem likely to hold within families, and not just between families. Although Schoenemann et al (2000) found a zero within-family correlation between intelligence and brain size in 36 young adult twin pairs, Wickett, Vernon, and Lee (1997) found a within-family correlation of +.25 in 34 adult male siblings. Recent work (Pennington et al, 2000;Posthuma et al, 2002Posthuma et al, , 2003 also shows a substantial positive genetic correlation between intelligence and brain size, confirming within-family effects.…”
Section: Does Brain Size Correlate With Intelligence?mentioning
confidence: 97%
“…The relation between brain structure and cognition has been studied in genetic informative samples in adults (Carmelli, Swan, DeCarli, & Reed, 2002;Schoenemann, Budinger, Sarich, & Wang, 2000;Thompson et al, 2001;Tramo et al, 1998;Wickett et al, 2000). ), Hulshoff Pol et al (2006 and Posthuma et al (2003) showed in a sample of 135 individuals (existing of twins and siblings coming from 60 twin families) that the relationship between full scale IQ and WMV and GMV is completely mediated by genetic factors, as well as the relationship between verbal IQ and performal IQ and several focal GM and WM areas.…”
Section: A Genetic Analysis Of Brain Volumes and Iq In Childrenmentioning
confidence: 99%